Sportsmanship attitudes in young adolescents from post-communist countries - Bronikowski, Michał; Bronikowska, Małgorzata; Laudańska-Krzemińska, Ida; Glapa, Agata; Morina, Besnik (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Students’ moral development is one of the main educational goals of physical education curricula. Aim of Study. This study is an attempt at identifying what attitudes toward sportsmanship behavior are held by young adolescents from post-communist countries. Material and Methods. The sample included data from 547 boys and girls, aged 13-15, selected from schools in Poznan (Poland), Kustandil (Bulgaria), and Pristina (Kosovo). The study concerned sportsmanship dilemmas in three areas of moral development: judgment, reasoning, and intentions. The level of moral development was determined using the Horrocks Prosocial Play Behavior Inventory. Results. No significant effect was found in moral judgment, reasoning, and intentions between the teenagers from the examined countries. Conclusions. The findings suggest that the level of moral development of students in the three countries is similar
Keywords: sportsmanship; moral development; young adolescents; physical education